2022
DOI: 10.1002/cbin.11836
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CXCR4 to suppress glioma‐initiating cells and chemoresistance in glioma

Abstract: Glioma initiating cells (GICs), also known as glioma stem cells, display the capacity to recapitulate the functional diversity within the tumor. Despite the great progress achieved over the last decades, defining the key molecular regulators of GICs has represented a major obstacle in this field. In our study, data from The Cancer Genome Atlas database illustrated a relationship between C‐X‐C motif chemokine receptor 4 (CXCR4) expression and the survival of glioma patients. Mechanistically, we further indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…According to the research conducted by Wu et al [14], it was discovered that increasing the expression of CXCR4 enhanced the migratory and invasive capabilities of U251 cells, which are brain glioma cells. The CXCR4regulated Akt pathway is an important link in promoting the growth and migration of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…According to the research conducted by Wu et al [14], it was discovered that increasing the expression of CXCR4 enhanced the migratory and invasive capabilities of U251 cells, which are brain glioma cells. The CXCR4regulated Akt pathway is an important link in promoting the growth and migration of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…According to Ohtaki et al (2017) , ACTC1 is as an independent prognostic and aggressive marker of gliomas. In addition, Wu et al (2022) demonstrated that CXCR4 promotes the proliferation of GICs through the KLF5/BCL2L12-dependent pathway. These essential cluster genes may have good predictive efficacy for glioblastoma and are essential for glioblastoma development.…”
Section: Discussionmentioning
confidence: 99%
“…Among the several molecular signaling pathways, the expression of SDF-1α/CXCR4 is also a key determinant of other glioma subtypes, causing devasting tumor progression and invasiveness [ 141 ].…”
Section: Chemokine-targeting Therapies In Primary Brain Cancersmentioning
confidence: 99%